Long-chain n-3 fatty acids and inflammation: potential application in surgical and trauma patients - Calder P.C. (Brazilian Journal of Medical and Biological Research, 2003)
Lipids used in nutritional support of surgical or critically ill patients have been based on soybean oil, which is rich in the n-6 fatty acid linoleic acid (18:2n-6). Linoleic acid is the precursor of arachidonic acid (20:4n-6). In turn, arachidonic acid in cell membrane phospholipids is the substrate for the synthesis of a range of biologically active compounds (eicosanoids) including prostaglandins, thromboxanes, and leukotrienes. These compounds can act as mediators in their own right and can also act as regulators of other processes, such as platelet aggregation, blood clotting, smooth muscle contraction, leukocyte chemotaxis, inflammatory cytokine production, and immune function. There is a view that an excess of n-6 fatty acids should be avoided since this could contribute to a state where physiological processes become dysregulated. One alternative is the use of fish oil. The rationale of this latter approach is that fish oil contains long chain n-3 fatty acids, such as eicosapentaenoic acid. When fish oil is provided, eicosapentaenoic acid is incorporated into cell membrane phospholipids, partly at the expense of arachidonic acid. Thus, there is less arachidonic acid available for eicosanoid synthesis. Hence, fish oil decreases production of prostaglandins like PGE2 and of leukotrienes like LTB4. Thus, n-3 fatty acids can potentially reduce platelet aggregation, blood clotting, smooth muscle contraction, and leukocyte chemotaxis, and can modulate inflammatory cytokine production and immune function. These effects have been demonstrated in cell culture, animal feeding and healthy volunteer studies. Fish oil decreases the host metabolic response and improves survival to endotoxin in laboratory animals. Recently clinical studies performed in various patient groups have indicated benefit from this approach.